Negative reciprocity and retrenched pension rights - Raymond Montizaan; Frank Cörvers; Andries de Grip; Thomas Dohmen (Institute for the Study of Labor (IZA), 2012)
We document the importance of negatively reciprocal inclinations in labor relationships by showing that a retrenchment of pension rights, which is perceived as unfair, causes a larger reduction in job motivation the stronger workers' negatively reciprocal inclinations are. We exploit unique matched survey and administrative data on male employees in the public sector in the Netherlands and compare the job motivation of employees born in 1950, who faced a substantial retrenchment of their pension rights resulting from a pension reform in 2006, to that of slightly older employees who remain entitled to more generous pension benefits. Job motivation is significantly lower among negatively reciprocal employees who were affected by the reform. The negative effect on job motivation is greater for negative reciprocal employees born very shortly after the cut-off date of January 1, 1950, as well as for those with many untreated colleagues, and who therefore arguably perceive the policy change as being more unfair. We also find that the treatment effect is stronger among workers who are more likely to hold their employer accountable for the drop in their pension rights, that is, those who work for the national government.
Keywords: D63; J2; 330; reciprocity; job motivation; retrenchment of pension rights; Ruhegehalt; Rentenreform; Austauschtheorie (Soziologie); Leistungsmotivation; Öffentlicher Dienst; Niederlande